2020
DOI: 10.17853/1994-5639-2020-4-89-109
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of students’ emotional intelligence and the level of their readiness for online education: A contextual study on the example of university training in Saudi Arabia

Abstract: Introduction. It is well known that the effectiveness of students’ online education depends largely on their skills to interact with the digital educational environment. At the same time, there has been a marked shift in scientific publications from the traditional point of view about the priority of competency formation in students to use educational information and communication technologies on the other aspects of online education, including psychometric.<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
1
35
1
2
Order By: Relevance
“…Discussing the results obtained, it can be assumed that in the situation of forced distance learning during the summer session, the system of personal senses and related actual psychoemotional states affects the activity of the zone of singularity of sense and undergoes a change, subjectively perceived as tension and mental activation. Continuing the discussion, according to studies, as a result of depletion of resources, especially in connection with the efforts made to volitional control over the situation, the ability to psychological well-being and self-regulation is significantly reduced [5,16,17,19]. Table 3 below shows the results of the correlation analysis.…”
Section: Key Results and Discussionmentioning
confidence: 96%
“…Discussing the results obtained, it can be assumed that in the situation of forced distance learning during the summer session, the system of personal senses and related actual psychoemotional states affects the activity of the zone of singularity of sense and undergoes a change, subjectively perceived as tension and mental activation. Continuing the discussion, according to studies, as a result of depletion of resources, especially in connection with the efforts made to volitional control over the situation, the ability to psychological well-being and self-regulation is significantly reduced [5,16,17,19]. Table 3 below shows the results of the correlation analysis.…”
Section: Key Results and Discussionmentioning
confidence: 96%
“…The revealed relationships of emotional intelligence with practical mathematical thinking, mathematical generalization and combinatorial abilities make it relevant to address modern research on emotional intelligence. It is shown that a high level of emotional intelligence increases the level of subjective well-being (Por et al, 2011), is positively associated with life satisfaction, self-esteem and self-acceptance (Carmeli et al, 2009), and readiness for online learning (Alenezi, 2020). Djermanov and Marić Jurišin (2018) point out the importance of emotional literacy in education and the need for pedagogical monitoring of the emotional development of young people, the development of their emotional competence directly in the system of education.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of learning outcomes is one of the main issues in education. Over recent years, there has been an increasing interest in this issue due to the development of elearning methods, and new learning models (massive open online courses) [10] require tools and measures that allow teachers to effectively and reliably evaluate large groups of students. Researchers come up with various solutions, including measures to obtain information on student interaction, didactic resources, and tools that can provide information on the student learning path [11].…”
Section: Introductionmentioning
confidence: 99%